The marbled crayfish (Decapoda: Cambaridae) represents an independent new species - Lyko, Frank (Zootaxa, 2017)
Marbled crayfish are a globally expanding population of parthenogenetically reproducing freshwater decapods. They are closely related to the sexually reproducing slough crayfish, Procambarus fallax, which is native to the southeastern United States. Previous studies have shown that marbled crayfish are morphologically very similar to P. fallax. However, different fitness traits, reproductive incompatibility and substantial genetic differences suggest that the marbled crayfish should be considered an independent species. This article provides its formal description and scientific name, Procambarus virginalis sp. nov.
Gesehen am 24.10.2018